Pollen Transport and Size of Main Flower Visitors of Rapeseed in the Southern Pampas Phytogeographic Region - Luciano Alberto Marinozzi; Soledad Camila Villamil (EUNK Revista Científica de Abejas y Apicultores)
The number of pollen grains deposited by pollinators on flowers during each visit depends on the morphological characteristics of both the flower and the insect, as well as their behavior, and can vary widely among taxa. This study investigated the relationship between the body size of the main flower visitors of rapeseed (Brassica napus L.) in the southern Pampas phytogeographic region and the amount of pollen adhered to their bodies, a key factor in determining their effectiveness as pollinators. Three groups of insects were analyzed: Apis mellifera, Campsomeris bistrimaculata, and a Halictidae morphospecies. Female C. bistrimaculata were the largest specimens, while the halictids were the smallest. The amount of pollen transported by A. mellifera, Halictidae, and female C. bistrimaculata exceeded 19,000 grains per individual, with no significant differences among these groups. Males of C. bistrimaculata transported significantly less pollen. The size of rapeseed flower visitors is highly variable and is associated with both taxon and sex of the individuals. The studied insects transport thousands of pollen grains on their bodies, and their presence on rapeseed flowers is a clear indication of their importance as pollinators.